Unifying Ulū Al-Albāb Approach of Strategic Planning in Sustaining Competitive Advantage of Social Enterprises - Suhaimi Mhd Sarif; Yusof Ismail; Dolhadi Zainudin (Journal of Islamic Management Studies, 2022)
This paper explores on the ulū al-albāb approach of strategic planning in sustaining competitive advantage of social enterprises. The conventional approach of strategic planning in sustaining competitive advantage of social enterprises is based on reasoning, experience, and intuition. The ulū al-albāb approach offers unification of soul into reasoning, experience, and intuition. The soul dimension manifests the submission to the obligation as servants (‘ibād al-Rahmān) and vicegerents of Allah (khālifah Allah fi al-ard). This paper argued that the ulū al-albāb approach of strategic planning unifies soul dimension into reasoning, experience, and intuition through the ulū al-albāb approach. The ulū al-albāb approach empowers soul to reasoning, experience, and intuition in strategic planning to sustain competitive advantage for social enterprises. The results of the paper are based on personal interviews with 15 informants. The ulū al-albāb approach in strategic planning practiced by the social enterprises can be divided into early adoption, seasonal adoption, and regular adoption. The early adoption refers to the integration of soul and reasoning within the standards and practices. The seasonal adoption refers to the integration of soul beyond standards and practices with the emphasis of congregational (jamaah) mindedness. As for the regular adoption refers to the integration of soul into strategic planning as way of life. The informants argued that there are at least three ways of ulū al-albāb approach in strategic planning to sustain competitive advantage for social enterprises.